2008
DOI: 10.1007/s12149-008-0151-2
|View full text |Cite
|
Sign up to set email alerts
|

The clinical efficacy of 18F-FDG-PET/CT in benign and malignant musculoskeletal tumors

Abstract: (18)F-FDG-PET/CT reliably differentiated malignant soft tissue and bone tumors from benign ones, although there were many false-positive and false negative lesions. Further studies with all kinds of musculoskeletal tumors in large numbers are needed to improve the diagnostic accuracy of (18)F-FDG-PET/CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
57
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(59 citation statements)
references
References 20 publications
1
57
1
Order By: Relevance
“…Of the 1,310 articles screened, 16 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) were selected for the final analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 1,310 articles screened, 16 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) were selected for the final analysis (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, the use of PET imaging in the differential diagnosis between benign and malignant bone tumours has been debated because high accumulation of fludeoxyglucose (FDG) can be observed in some benign bone lesions, especially histiocytic or giant cell containing lesions [6]. Previous studies have reported that the maximal standardised uptake value (SUV max ) of haemangioma was less than 2.5 on fluorine-18-FDG ( 18 F-FDG) PET/CT [6][7][8][9]. To our knowledge, these atypical 18 F-FDG PET/CT findings of intra-osseous haemangioma have not been previously reported.…”
mentioning
confidence: 99%
“…Positron emission tomography (PET) using 18 F FDG is being used along with computed tomography (CT) and magnetic resonance imaging (MRI) in differentiation of benign and malignant intraosseous lesions. Nuclear medicine physicians should be aware of a high accumulation of FDG in some benign bone tumors and tumor like lesions, specially histocytic and Giant cell containing lesions.…”
Section: Resultsmentioning
confidence: 99%
“…Nuclear medicine physicians should be aware of a high accumulation of FDG in some benign bone tumors and tumor like lesions, specially histocytic and Giant cell containing lesions. Dual-time point 18 F FDG PET may provide more help in this differentiation and is specially recommended for the unclear bone lesions.…”
Section: Resultsmentioning
confidence: 99%